KAJIAN KRITIS TERHADAP PESERTA LOMBA FLS2N CABANG TARI TINGKAT SMP TAHUN 2019 DI PROVINSI SUMATERA BARAT - Venny Rosalina; Fabio Yuda (Melayu Arts and Performance Journal, 2020)
FLS2N is one of the most prestigious competency events in the West Sumatra region. The event provided a platform to continue to hone creativity and develop West Sumatra typical dances. Traditional Minangkabau values are one of the creative sources in packaging the dances that are presented in the competition stems at FLS2N. This study aims to analyze the extent to which the development of dance offerings in dance competition participants in West Sumatra Province. The focus of this research is the winners of the junior high school dance branch in 2019 in West Sumatra Province. This research is a qualitative research with a case study approach, with data collected through direct observation and interview techniques. The results of the study show that seen from critical fist, the dance performances of the winners of the competition at the West Sumatra Province level in 2019 still use motion patterns that tend to repeat old styles and forms. That is, choreologically, it tends not to be well developed. Meanwhile, there is still a tendency for many dance numbers to give less space to female dancers. It is an unfortunate fact that considering history shows that in fact female choreographers were the developers of contemporary Minangkabau dance.ABSTRAKFLS2N Cabang Tari adalah salah satu ajang kompetensi yang bergensi diwilayah Sumatera Barat. Acara tersebut memberikan sebuah wadah untuk terus mengasah kreativitas dan mengembangkan tarian-tarian khas Sumatera Barat. Nilai-nilai tradisional Minangkabau merupakan salah satu sumber kreatif dalam mengemas tari-tari yang disajikan pada tangkai lomba di FLS2N. Penelitian ini bertujuan untuk menganalisis sejauh mana perkembangan sajian tari pada peserta lomba cabang tari di Provinsi Sumatera Barat. Fokus penelitian ini adalah para pemenang dari cabang tari tingkat SMP pada Tahun 2019 di Provinsi Sumatera Barat. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus,dengan data yang dikumpulkan melalui Teknik pengamatan langsung dan wawancara. Hasil penelitian menunjukkan bahwa dilihat dari tinjuan kritis, maka sajian tari para pemenang lomba di tingkat Provinsi Sumatera Barat Tahun 2019 masih mengunakan pola gerak yang cenderung mengulang-ulang gaya dan bentuk yang lama. Artinya, secara koreologi cenderung tidak berkembang baik. Sementara itu, masih terdapat kecenderungan banyak nomor tarian yang kurang memberi tempat pada para penari perempuan.Kata Kunci: FLS2N, Tari Minangkabau, Kajian Kritis, Koreologi, Minangkabau